Preclinical feasibility of robot‐assisted sentinel lymph node biopsy using multi‐modality magnetic and fluorescence guidance in the head and neck. Issue 12 (8th September 2022) - Krishnan, Giri; Cousins, Aidan; Pham, Nguyen; Milanova, Valentina; Nelson, Melanie; Krishnan, Shridhar; van den Berg, Nynke S.; Shetty, Anil; Rosenthal, Eben L.; Wormald, Peter‐John; Thierry, Benjamin; Foreman, Andrew; et al.
Abstract: Background: Sentinel lymph node biopsy (SLNB) is a staging procedure dependent on accurate mapping of draining lymphatics via tracers. Robot‐assisted SLNB enables access to multiple neck levels with a single incision and intraoperative fluorescence guidance to the SLN. Methods: Lymphatic mapping in swine was done using a magnetic tracer and fluorescent dye, injected into the tongue. MRI preoperatively mapped lymphatic spread of the magnetic tracer. Dissection was performed using a da Vinci Xi robot guided by fluorescence‐imaging of the dye. Results: Robot‐assisted SLNB was successfully performed in all animals ( n = 5). A novel MRI protocol differentiated SLNs ( n = 6) from lower echelon nodes ( n = 11) based on flow progression. Fluorescence imaging provided valuable intraoperative guidance and correlated with magnetic‐positive nodes. Conclusions: This study demonstrates preclinical feasibility of a robot‐assisted approach to SLNB using magnetic and fluorescent tracers in the head and neck, enabling both preoperative mapping and intraoperative guidance.